2015
DOI: 10.1007/s10649-015-9594-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of teaching mathematics and learning achievement gains: evidence from primary schools in Kenya

Abstract: This paper examines the contribution of quality mathematics teaching to student achievement gains. Quality of mathematics teaching is assessed through teacher demonstration of the five strands of mathematical proficiency, the level of cognitive task demands, and teacher mathematical knowledge. Data is based on 1907 grade 6 students who sat for the same test twice over an interval of about 10 months. The students were drawn from a random selection of 72 low-and high-performing primary schools. Multi-level regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
12
1
2
Order By: Relevance
“…This finding is also in tandem with the work of Herman (2000) who investigated the development and management of quality assurance in higher education systems and institutions in Asia and the Pacific and discovered that several higher education institutions in Asia have weak institutional quality assurance mechanisms that make it difficult for them to guarantee the quality of their products and processes. This is not any different with the findings of Ngware, Ciera, Musyoka and Oketch (2015) who reported that "the average performance in quality education of African countries appears much poorer than elsewhere in the world. …One way of improving the quality of education is through quality teaching" (p.1).…”
Section: Discussion Of Findingscontrasting
confidence: 61%
“…This finding is also in tandem with the work of Herman (2000) who investigated the development and management of quality assurance in higher education systems and institutions in Asia and the Pacific and discovered that several higher education institutions in Asia have weak institutional quality assurance mechanisms that make it difficult for them to guarantee the quality of their products and processes. This is not any different with the findings of Ngware, Ciera, Musyoka and Oketch (2015) who reported that "the average performance in quality education of African countries appears much poorer than elsewhere in the world. …One way of improving the quality of education is through quality teaching" (p.1).…”
Section: Discussion Of Findingscontrasting
confidence: 61%
“…Therefore, teachers need to consider what is given by researchers in order to improve the learning process. Ngware, Ciera, Musyoka, and Oketch (2015) also state the quality of the teacher positively contributes to improving student learning achievement. Moreover, Ottmar, Decker, Cameron, Curby, and Rimm-Kaufman (2014) reveal different research results that there is no relationship between the quality of learning with an increase in student achievement.…”
Section: Discussionmentioning
confidence: 97%
“…Effective teaching, Ngware, Ciera, Musyoka, and Oketch (2015) is achieved with proficiency in conditional knowledge of related subjects, mastery of content, proper integration of experimental segments of topics covered which in turn encourages learners to go beyond state of competency goals and achieve academically. Hence, application of experiential learning is ideal within practice tailored to curriculum through teaching basic subjects, lesson planning, structuring of learning objectives and in instructional management.…”
Section: Experiential Learning and Conditional Knowledge In Teaching mentioning
confidence: 99%